THE MEDIATING ROLE OF FAIRNESS AND MANAGEMENT ACCOUNTING SYSTEMS IN MANAGERIAL PERFORMANCE - Buchori, Imam; Muflihin, Mohammad; Hidayat, Ahmad Agus (JRAK, 2025)
Managerial performance is a crucial and primary component in enhancing achievements in management. The research aims at empirically examining the effect of Budget Congruence on Managerial Performance, mediated by Procedural Fairness, Distributive Fairness, and Management Accounting Systems at  Islamic State Universities (PTKIN) with public service agency status in East Java. Using a quantitative approach, the respondents were leaders at Islamic State Universities in East Java Province, Indonesia. The findings showed that Budget Congruence significantly impacted Procedural Fairness, Distributive Fairness, and the Management Accounting System. Procedural Fairness and Distributive Fairness could mediate the effect of Budget Congruence on Managerial Performance, while the Management Accounting System failed to mediate the relationship between Budget Congruence and Managerial Performance. These findings highlighted the importance of budget congruence in enhancing procedural fairness and distributive fairness, which ultimately could improve managerial performance.